Procesowe konsekwencje postanowień kończących postępowanie sądowe przed rozprawą główną - Adamczak, Ireneusz (Wydział Prawa i Administracji UAM, 1982)
The article discusses two important questions regarding the subject matter from the litigious angle, namely whether the rulings bringing the legal proceedings to an end before the main trial are barring the way to deliver a judgement or they altogether end the proceedings regarding the given case. The author is of an opinion that the analysed rulings are barring the way to deliver a judgement i. e. they end the proceedings, still the judgement can be passed in new legal proceedings properly instituted or in the court of competent justice. The way to deliver a judgement is not barred by these decisions in an identical way. Rulings of termination, of lack of jurisdiction or of conditional quashing of criminal proceedings are finally barring the way to pass a judgement in the given court. While rulings returning the case to complete preparatory proceedings are barring that way only temporarily. The author observes that the rulings of quashing and of conditional quashing of the criminal proceeding reveal traits of decisions terminating the proceedings regarding the case in hand. The decisions end the primary proceedings in the sense that they preclude any possibility of going further through the usual channels of instances.
Litigious Consequences of Rulings Terminating the Legal Proceedings before the Main Trial